Ta’līm al-Lugah Al-‘Arabiyyah al-Qāim ‘alā Bulūkait fī Itqān al-Mufradāt al-‘Arabiyyah liṭullab al-Madrasah al-‘Āliyyah - Sandra, Putri Nadira; Herni, Zulfiana (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This research aims to analyze the effectiveness of using Blooket digital learning media in improving Arabic vocabulary mastery in class X MAS Cipta Simpang Dolok students. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. In this study, the following data and data sources were the informants: Arabic language teachers and students. The data is written, while the unwritten data is: if using observation, the data source is the process of something, and written research. If using documentation, then the documents or notes are the data sources, the data is divided into two, the first is: primary data, or data obtained from teachers, while the second is: secondary data in the form of lesson plans, journals. The data population is: all students of class X MAS Cipta Simpang Dolok, while the sample is: ten students of class X MAS Cipta Simpang Dolok who were selected as participants to measure the effectiveness of block-based learning on Arabic vocabulary mastery. The data analysis technique used in this study is descriptive qualitative analysis, which involves reducing the data, presenting the data, and drawing conclusions. The research results show that using Blooket, which uses a gamification approach, can increase student The data analysis technique used is the analytical descriptive method, which describes the data collected in the form of words, images, and not numbers. Data from interviews, field notes, documents, and so on, are then described so that they can provide clarity on reality. According to Miles and Huberman's theory, there are three data analysis techniques: data reduction, data presentation, and concluding. tivation and engagement during the learning process. Repetition through interactive games has proven to be more effective in helping students remember and understand the meaning of vocabulary than traditional memorization methods; thus, Blooket can be an innovative alternative media in technology-based Arabic language learning.